Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015; Session “Circulation, O2 Transport and Haematology” - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2015)
Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015 ORGANIZING INSTITUTIONS European Society for Neonatology (ESN), European Society for Paediatric Research (ESPR), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI), with the local host of Hungarian Society of Perinatology and Obstetric Anesthesiology, Hungarian Society of Perinatology (MPT), supported by Council of International Neonatal Nurses (COINN), organizing secretariat MCA Scientific Events PROGRAMME COMMITTEE Artúr Beke (Hungarian Society), Morten Breindahl (ESN), Giuseppe Buonocore (UENPS), Pierre Gressens (ESPR), Silke Mader (EFCNI), Manuel Sánchez Luna (UENPS), Miklós Szabó (Hungarian Society of Perinatology), Luc Zimmermann (ESPR) Session “Circulation, O2 Transport and Haematology” ABS 1. TRANSITIONAL CHANGES IN CEREBRAL BLOOD VOLUME OF TERM AND PRETERM INFANTS WITH AND WITHOUT RESPIRATORY SUPPORT AFTER BIRTH • B. Schwaberger, G. Pichler, A. Avian, C. Binder-Heschl, N. Baik, B. Urlesberger ABS 2. HEMATOLOGIC ABNORMALITIES IN THE FIRST 72 HOURS OF LIFE IN SMALL-FOR-GESTATIONAL-AGE PRETERM NEWBORNS • A. Matic, A. Ristivojevic ABS 3. THE ANTICOAGULANT ACTION OF ACTIVATED PROTEIN C IN VERY PRETERM INFANTS • E. Neary, N. McCallion, B. Kevane, K. Egan, M. Cotter, F. Ni Ainle ABS 4. SURVIVAL AFTER CARDIAC ARREST IN THE NEONATAL INTENSIVE CARE UNIT • E. Foglia, R. Langeveld, L. Heimall, A. Deveney, A. Ades, E. Jensen ABS 5. A PATENT DUCTUS ARTERIOSUS SEVERITY SCORE INCORPORATING MARKERS OF HAEMODYNAMIC SIGNIFICANCE AND LEFT VENTRICLE DIASTOLIC FUNCTION PREDICTS CHRONIC LUNG DISEASE • A.T. James, J.D. Corcoran, P. Dicker, O. Franklin, Y.N. Elsayed, J. Ting, A. Sehgal, A. Malikawi, A. Harabor, A.S. Soraisham, P.J. McNamara ABS 6. A STUDY TO VALIDATE THE DURATION OF ASSESSMENT OF BASELINE NIRS VALUES IN PRETERM BABIES WITH ECHOCARDIOGRAPHICALLY-CONFIRMED PDA • C. Kotidis, M. Turner ABS 7. HAEMODYNAMICS IN PRETERM INFANTS WITH PATENT DUCTUS ARTERIOSUS (HAPI-PDA STUDY): A PILOT STUDY • C. Kotidis, N. Subhedar, M. Weindling, M. Turner ABS 8. SKIN MICROCIRCULATION IN ASPHYXIATED NEWBORNS TREATED WITH HYPOTHERMIA • S. Fredly, D. Fugelseth, C.S. Nyggard, T. Stiris, K. Kvernebo ABS 9. PLETH VARIABILITY INDEX IN PRETERM INFANTS: IS IT FEASIBLE? • H.A. van Elteren, T.G. Goos, I.K.M. Reiss, R.C.J. de Jonge, V.J. van den Berg ABS 10. VALIDITY OF BIOMARKERS ON CARDIOVASCULAR SUPPORT (CVS): AN ANALYSIS IN RETROSPECT • A. Pellicer, M.C. Bravo, P. López-Ortego, L. Sanchez, R. Madero, F. Cabañas; the Neocirculation Study Group ABS 11. PILOT STUDY OF DOBUTAMINE (DB) VERSUS PLACEBO (PL) FOR EARLY LOW SUPERIOR VENA CAVA (SVC) FLOW: LONG-TERM OUTCOME • M.C. Bravo, P. López-Ortego, L. Sánchez, R. Madero, F. Cabañas, A. Pellicer ABS 12. THROMBOELASTOGRAPHYCAL ASSESSMENT OF THE HEMOSTATIC SYSTEM IN NEWBORNS WITH PERIVENTRICULAR HEMORRHAGE • K. Leonava ABS 13. THE EFFECT OF ANTENATAL MAGNESIUM SULFATE ADMINISTRATION ON LEFT VENTRICULAR AFTERLOAD AND MYOCARDIAL PERFORMANCE MEASURED USING DEFORMATION AND ROTATIONAL MECHANICS IMAGING • J.D. Corcoran, B. Hayes, O. Franklin, A. EL-Khuffash ABS 14. THE EFFECT OF MATERNAL ANTIHYPERTENSIVE DRUGS ON CEREBRAL, RENAL AND SPLANCHNIC OXYGEN EXTRACTION IN PRETERM BORN NEONATES • A.E. Richter, T.E. Schat, K.N.J.A. Van Braeckel, A.F. Bos, E.M.W. Kooi ABS 15. SERUM NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN AS AN EARLY MARKER OF ACUTE KIDNEY INJURY IN NEONATES WITH HYPOPLASTIC LEFT HEART SYNDROME • P. Surmiak, M. Baumert, Z. Walencka, A. Witek ABS 16. A PROSPECTIVE STUDY INTO THE GENERATION OF INDIVIDUALISED OPTIMAL MEAN ARTERIAL BLOOD PRESSURE (MABP) MEASUREMENTS USING NEAR-INFRARED SPECTROSCOPY (NIRS) IN THE PRETERM NEONATE • G. Stevenson, C. Costa, M. Czosnyka, P. Smielewski, T. Austin ABS 17. THE EFFECTS OF SKIN-TO-SKIN ON PLACENTAL TRANSFUSION: A NONRANDOMIZED PILOT CONTROLLED TRIAL • D. Erickson-Owens, J. Mercer, D. Thulier, W. Oh, M. VanVleet ABS 18. ASSOCIATION BETWEEN INDUCED LABOR AND FETAL STRESS HORMONE RELEASE • S. Wellmann, A. Koslowski, K. Spanaus, R. Zimmermann, T. Burkhardt ABS 19. ASSESSMENT OF PULMONARY HEMODYNAMIC FUNCTION IN PRETERM INFANTS: MATURATIONAL PATTERNS OF PULMONARY ARTERY ACCELERATION TIME • M.D. Patel, A.T. James, P.J. McNamara, A. Jain, O. Franklin, A. Mathur, C. Lee, A. Hamvas, G.K. Singh, L. Mertens, P.T. Levy ABS 20. LONGITUDINAL CARDIAC CHANGES IN PRETERM INFANTS WITH PROLONGED EXPOSURE TO A PATENT DUCTUS ARTERIOSUS • K. de Waal, N. Phad ABS 21. NOVEL NON-INVASIVE MEASUREMENTS IN THE ASSESSMENT OF NORMAL CARDIOVASCULAR ADAPTATION IN TERM & NEAR TERM INFANTS • L. Mahoney, D. Wertheim, J.R. Fernandez Alvarez, N. Aiton, H. Rojas-Anaya, P. Seddon, H. Rabe ABS 22. PERFUSION INDEX USED AS A SIXTH VITAL SIGN IN PRETERM INFANTS LEADS TO EARLY DIAGNOSIS OF SHOCK AND BETTER OUTCOMES • D. Hariharan, G. Veluswami, L. Balasubramanian, V. Kannappan, R.M. Sahadevan ABS 23. EARLY CIRCULATORY AND RESPIRATORY PARAMETERS IN EXTREMELY PRETERM INFANTS • K.W. Olsson, R. Sindelar, A. Jonzon ABS 24. UK SURVEILLANCE OF SURGICAL LIGATION OF THE PATENT DUCTUS ARTERIOSUS (PDA) IN PREMATURE BABIES PRIOR TO FIRST DISCHARGE HOME • A. Lakshmanan, L. Lee, T. Crosby, W. Kelsall ABS 25. CURRENT PRACTICES ON HEMODYNAMIC MONITORING IN NEONATAL INTENSIVE CARE: AN INTERNATIONAL SURVEY • S. Vrancken, L. Frijns, K. Liem, J. Hopman, J. Lemson, A. van Heijst, W. de Boode ABS 26. NON-INVASIVE ASSESSMENT OF DIASTOLIC MYOCARDIAL PROPERTIES IN ELBW NEONATES • T. Kovacs, G. Mogyorosy, A. Kertesz, A. Borbely, Z. Papp, Gy. Balla ABS 27. PRIOR CLINICAL DESCRIPTION BIASES ASSESSMENT OF CAPILLARY REFILL TIME • E. Murphy, S. Coleman, S. Hill, C. Henry, D. Morris, D. Sharkey ABS 28. AFTERLOAD REDUCTION IN CATECHOLAMINE-RESISTANT SHOCK IN EXTREME PREMATURITY: NOVEL THERAPY WITH OLD DRUG FOR AN UNRECOGNIZED FACTOR IN SHOCK • D. Hariharan, G. Veluswami, L. Balasubramanian, V. Kannappan, R. Sahadevan ABS 29. HEART FUNCTION ASSESSMENT IN ASPHYXIA; SPECKLE TRACKING ECHOCARDIOGRAPHY PERFORMS BETTER THAN TISSUE DOPPLER ECHOCARDIOGRAPHY AND FRACTIONAL SHORTENING • E. Nestaas, A. Støylen, D. Fugelseth ABS 30. GLOBAL RIGHT VENTRICULAR FRACTIONAL AREA CHANGE IS A SURROGATE MARKER FOR SYSTEMIC BLOOD FLOW IN PRETERM INFANTS • J.D. Corcoran, O. Franklin, A. EL-Khuffash ABS 31. HEART RATE VARIABILITY CHANGES ASSOCIATED WITH NEONATAL INFECTION • P. Amess, H. Rabe, D. Wertheim ABS 32. POINT OF CARE FUNCTIONAL ECHOCARDIOGRAPHIC INTER- AND INTRA-OBSERVER VARIABILITY: RIGHT VENTRICULAR OUTFLOW & SUPERIOR VENA CAVA FLOW IN WELL AND UNWELL NEWBORN INFANTS • L. Mahoney, J.R. Fernandez Alvarez, H. Rojas-Anaya, N. Aiton, D. Wertheim, P. Seddon, H. Rabe ABS 33. UK TRANSFUSION-ASSOCIATED NECROTISING ENTEROCOLITIS CASES IDENTIFIED THROUGH A MULTICENTRE AUDIT • S. Hamad, K. Jones, K. Sim, S. Cherian, A. James, S. Godambe, H. New, J.S. Kroll, P. Clarke ABS 34. LONGITUDINAL ASSESSMENT OF MYOCARDIAL STRAIN AND STRAIN RATE AND THE EFFECT OF CHRONIC LUNG DISEASE IN PRETERM INFANTS LESS THAN 29 WEEKS GESTATION • J.D. Corcoran, O. Franklin, L. Mertens, A. EL-Khuffash ABS 35. THE EFFECT OF PRENATAL CAFFEINE ON THE CARDIOVASCULAR TRANSITION AT BIRTH • C. Binder-Heschl, K. Crossley, G. Polglase, D. Blank, V. Zahra, A. Moxham, K. Rodgers, S. Hooper ABS 36. FEASIBILITY OF USING THE ELDON CARD IN THE PERIPARTUM DIAGNOSIS OF RH INCOMPATIBILITY BETWEEN MOTHERS AND THEIR NEWBORNS • B.Q. Goka, S.A. Obed, A.B. Akwasi-Kumah, I.O. Koranteng, M.A. Nuamah, V. Beyuo, S.A. Oppong, M. Torto ABS 37. HEME-OXYGENASE EXPRESSION FOLLOWING PRETERM BIRTH: EVIDENCE OF A FEED-FORWARD MECHANISM DRIVEN BY OXIDATIVE STRESS • R. Dyson, A. Abbas, K. Shepherd, M. Kelly, H. Palliser, I. Wright ABS 38. TEMPORAL CHANGES IN MICROVASCULAR FUNCTION FOLLOWING PRETERM BIRTH IN GUINEA PIGS • R. Rahman, R. Dyson, K. Wright, M. Berry ABS 39. EXPLORING CEREBRAL AUTOREGULATION (AR) IN MODERATE AND SEVERE NEONATAL HYPOXIC-ISCHEMIC ENCEPHALOPATHY (HIE) DURING WHOLE BODY HYPOTHERMIA (WBH) • P. López-Ortego, J. Riera, M.C. Bravo, L. Sanchez, R. Madero, E. Valverde, F. Cabañas, A. Pellicer ABS 40. PACAP CAN INFLUENCE THE VASCULAR CHANGES IN THE ANIMAL MODEL OF RETINOPATHY OF PREMATURITY • T. Kvarik, B. Mammel, D. Werling, A. Vaczy, D. Reglodi, T. Ertl, J. Gyarmati, T. Atlasz ABS 41. DOPAMINE INFUSION IMPROVES CEREBRAL AUTOREGUALTION IN NEWBORN PIGLETS • V.R. Eriksen, M. Rasmussen, G.H. Hahn, G. Greisen ABS 42. OPTIMAL MEAN ARTERIAL BLOOD PRESSURE IN PRETERM INFANTS WITH LESS THAN 24 HOURS OF AGE • C.S. da Costa, M Czosnyka, P. Smielewski, G. Stevenson, C. Kemp, T. Austin ABS 43. THE IMPACT OF PREMATURE LUNG DISEASE ON THE MATURATION OF CARDIAC PERFORMANCE IN THE FIRST YEAR OF LIFE: DISCERNING EARLY PREDICTIVE MARKERS OF CHRONIC LUNG DISEASE • P. Levy, A. Sanchez, T. Sekarski, M. Holland, A. Hamvas, G. Singh ABS 44. THE MYOCARDIAL ARCHITECTURE CHANGES DUE TO PERSISTENT PULMONARY HYPERTENSION OF THE NEWBORN IN AN OVINE ANIMAL MODEL • P. Agger, S. Lakshminrusimha, C. Laustsen, S. Gugino, J.R. Frandsen, M. Smerup, R.H. Anderson, V. Hjortdal, R.H. Steinhorn ABS 45. EFFECT OF WITHHOLDING FEEDS ON TRANSFUSION-RELATED ACUTE GUT INJURY IN PRETERM INFANTS – A RANDOMISED CONTROLLED TRIAL • S. Sahin, G.K. Kutman, O. Bozkurt, F.Y. Atay, F.E. Canpolat, N. Uras, S.S. Oğuz